Jet-cocoon geometry in the optically dark, very high energy gamma-ray burst 201216C. Issue 2 (18th April 2022) - Rhodes, L; van der Horst, A J; Fender, R; Aguilera-Dena, D R; Bright, J S; Vergani, S; Williams, D R A
ABSTRACT: We present the results of a radio observing campaign on GRB 201216C, combined with publicly available optical and X-ray data. The detection of very high energy (VHE, >100 GeV) emission by MAGIC makes this the fifth VHE GRB at the time of publication. Comparison between the optical and X-ray light curves show that GRB 201216C is a dark GRB, i.e. the optical emission is significantly absorbed and is fainter than expected from the X-ray detections. Our e -MERLIN data also shows evidence of diffractive interstellar scintillation. We can study the column density along the line of sight to the GRB in both the host galaxy, from the damped optical light curve, and the Milky Way, via scintillation studies. We find that the afterglow is best modelled using a jet-cocoon geometry within a stellar wind environment. Fitting the data with a multicomponent model, we estimate that the optical, X-ray, and higher frequency radio data before ∼25 d originates from an ultrarelativistic jet with an isotropic equivalent kinetic energy of (0.6–10) × 10 52 erg and an opening angle of ∼1–9°. The lower frequency radio emission detected by MeerKAT, from day 28 onwards, is produced by the cocoon with a kinetic energy that is between two and seven orders of magnitude lower (0.02–50) × 10 48 erg. The energies of the two components are comparable to those derived in simulations of such scenarios.